Prehospital emergency care in a humanitarian environment: an overview of the ethical considerations. Issue 6 (29th August 2022) - Prescott, Tim; May, S; Horne, S; Barnard, E
Abstract : Recent history has demonstrated that UK Defence personnel can be used, potentially with little notice, in humanitarian disaster zones. The provision of prehospital emergency care (PHEC) in a humanitarian environment requires an innovative approach to overcome the technical challenges of a resource-limited setting. In addition to technical challenges, prehospital practitioners working in a humanitarian environment can expect to be faced with ethically testing situations that they are not familiar with in their usual practice. The organisational and individual ethical decision-making burden can result in significant harms. Therefore, the aim of this paper is to discuss the ethical considerations relevant to providing PHEC during a humanitarian disaster in order that personnel can be more prepared to optimally deliver care. This is a paper commissioned as a part of the Humanitarian and Disaster Relief Operations special issue of BMJ Military Health .